If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 1)(3x + -2)(4x + 3) = 0 Reorder the terms: (1 + 2x)(3x + -2)(4x + 3) = 0 Reorder the terms: (1 + 2x)(-2 + 3x)(4x + 3) = 0 Reorder the terms: (1 + 2x)(-2 + 3x)(3 + 4x) = 0 Multiply (1 + 2x) * (-2 + 3x) (1(-2 + 3x) + 2x * (-2 + 3x))(3 + 4x) = 0 ((-2 * 1 + 3x * 1) + 2x * (-2 + 3x))(3 + 4x) = 0 ((-2 + 3x) + 2x * (-2 + 3x))(3 + 4x) = 0 (-2 + 3x + (-2 * 2x + 3x * 2x))(3 + 4x) = 0 (-2 + 3x + (-4x + 6x2))(3 + 4x) = 0 Combine like terms: 3x + -4x = -1x (-2 + -1x + 6x2)(3 + 4x) = 0 Multiply (-2 + -1x + 6x2) * (3 + 4x) (-2(3 + 4x) + -1x * (3 + 4x) + 6x2 * (3 + 4x)) = 0 ((3 * -2 + 4x * -2) + -1x * (3 + 4x) + 6x2 * (3 + 4x)) = 0 ((-6 + -8x) + -1x * (3 + 4x) + 6x2 * (3 + 4x)) = 0 (-6 + -8x + (3 * -1x + 4x * -1x) + 6x2 * (3 + 4x)) = 0 (-6 + -8x + (-3x + -4x2) + 6x2 * (3 + 4x)) = 0 (-6 + -8x + -3x + -4x2 + (3 * 6x2 + 4x * 6x2)) = 0 (-6 + -8x + -3x + -4x2 + (18x2 + 24x3)) = 0 Combine like terms: -8x + -3x = -11x (-6 + -11x + -4x2 + 18x2 + 24x3) = 0 Combine like terms: -4x2 + 18x2 = 14x2 (-6 + -11x + 14x2 + 24x3) = 0 Solving -6 + -11x + 14x2 + 24x3 = 0 Solving for variable 'x'. The solution to this equation could not be determined.
| 70=5(2n-8) | | 1/4(4*-9-8)+4=3*-9+20 | | -25-8x=-6x+17 | | 50m-3=5m+132 | | -5(x-4)+3=16 | | 8b+2x=6x-4a | | 5+a+a=196 | | -33=5p+30 | | 2(7x+4)=6(2-x)+7 | | 5(9/5d+12)=9d-12 | | -16+2x=5x+32 | | 8+7x=-3x+68 | | 28a+5=4a+77 | | 20x^3y^2-25x^2y^2= | | -2(3x+1)-3(4x-2)=22 | | (4x^2-x+1)(1-3x-x^2)= | | 2x+9=37 | | 9=18+6w | | -4(-8+7x)=32 | | 18e-18=8e+2 | | 4x/5=90 | | 125x-27=0 | | 2y+18=8 | | 7u+51=4u+342 | | y=8/3*2.6667+8 | | 13r-7=5r+89 | | 3-5*a=25 | | 8a+23=a+107 | | a/8-17=-15 | | f(x)=x^2-8x-48 | | -4x-82=9x+126 | | 7(2-7x)=-280 |